Germany : Financial Sector Assessment Program-Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This paper evaluates the risks and vulnerabilities of the German financial system and reviews both the German regulatory and supervisory framework and implementation of the common European framework insofar as it is relevant for Germany. The country is home to two global systemically important financial institutions, Deutsche Bank AG and Allianz SE. The system is also very heterogeneous, with a range of business models and a large number of smaller banks and insurers. The regulatory landscape has changed profoundly with strengthened solvency and liquidity regulations for banks (the EU Capital Requirements Regulation and Directive IV), and the introduction of macroprudential tools.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet